River Discharge Derived of Lijiang River Basin Based on Sentinel-1 SAR Data - CHEN Siyu; LI Jiqing; XIE Yutao; TIAN Yu (Renmin Zhujiang)
As a new type of detection method developed based on the theory of electromagneticwaves, remote sensing technology has the advantages of non-contact observation, low measurementcost and wide coverage, which has opened up new ideas for the measurement of river discharge.Based on the Sentinel-1 SAR remote sensing image covering the Lijiang River Basin from August 2018to July 2019, the image was obtained every 12 days for a total of 29 groups of 58 scenes. Theartificial threshold segmentation method was used to extract the average river width of the waterbody along the Lijiang River. It is divided into 8 river sections, and the river discharge datafrom three corresponding hydrological stations of Darong River, Guilin and Yangshuo are used forone-dimensional regression analysis to establish the average river width-discharge regressionequation. Comparing the modeling effect of each river section, the best modeling sectioncorresponding to each station is obtained, with R2 of 0.92, 0.94 and 0.88 respectively. To verifyits empirical formula, the average deviation of river discharge inversion is at least 10%. It hasa good application effect in the river section with wider river channel and slower terrain. It canrealize the river discharge inversion based on remote sensing technology.